Extensive and predominant In Situ component in breast carcinoma: their influence on treatment results after breast-conserving therapy - Sinn, Peter; Anton, Hans-Werner; Magener, Achim; Fournier, Dietrich von; Bastert, Gunther; Otto, Herwart F. (European journal of cancer, 1998)
Intramammary tumour recurrence is one of the most important problems in breast-conserving therapy. We reviewed a series of 957 patients treated with breast-conserving therapy for primary invasive breast carcinomas between 1 January 1985 and 31 December 1992 at the University of Heidelberg. All histological slides were re-evaluated for risk factors with special emphasis on the extent and subclassification of the in situ tumour and the margin status. Six parameters were identified as significant risk factors for intramammary recurrence in the univariate analysis, including extensive or predominant in situ component (EIC, with at least twice the greatest dimension of the invasive tumour component), histological grade, angioinvasion, lobular tumour type, involved resection margin and lymph node status. The presence of an EIC was statistically correlated with low tumour grade, tumour at the resection margins and in re-excision specimens and with multifocal tumour invasion. Multivariate logistic regression analysis revealed that EIC (relative risk (RR)=1.9), tumour grade (RR=1.76), angioinvasion (RR=1.34), lobular tumour type (RR=1.65) and young age (≤40 years, RR=1.39) were independent predictors of local recurrence. When combining these factors in a linear model, the simultaneous presence of at least two of the five risk factors predicted a 5-year risk of intramammary recurrence of 20.9% compared with a risk of only 1-5% when none or one of these risk factors were identifiable. We conclude that the risk of subsequent intramammary recurrence after breast-conserving therapy can be estimated from a scoring system that includes four histological risk factors and the patient’s age.
Gesehen am 12.03.2024